Respuesta :

Simplifying

2.1x + -1(1 + 4.2x) = 5.3

2.1x + (1 * -1 + 4.2x * -1) = 5.3

2.1x + (-1 + -4.2x) = 5.3

Reorder the terms:

-1 + 2.1x + -4.2x = 5.3

Combine like terms: 2.1x + -4.2x = -2.1x

-1 + -2.1x = 5.3

Solving

-1 + -2.1x = 5.3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.

-1 + 1 + -2.1x = 5.3 + 1

Combine like terms: -1 + 1 = 0

0 + -2.1x = 5.3 + 1

-2.1x = 5.3 + 1

Combine like terms: 5.3 + 1 = 6.3

-2.1x = 6.3

Divide each side by '-2.1'.

x = -3

Simplifying

x = -3

Hope i was helpful!